2012
DOI: 10.1139/b11-064
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional gender polymorphisms in a population of the hermaphroditic lowbush blueberry (Vaccinium angustifolium)1This article is part of a Special Issue entitled “A tribute to Sam Vander Kloet FLS: Pure and applied research from blueberries to heathland ecology”.

Abstract: Lowbush blueberry (Vaccinium angustifolium Aiton) is a wild, but cultivated for profit, agricultural system grown primarily in the northeastern regions of North America. It has been suggested that a functional gender specialization may be occurring in this hermaphroditic species in which some individuals (termed clones) effectively function as bearers (high ovule production but little or nonviable pollen) or as pollen donors (low ovule number with high quantities of viable pollen). The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In this hermaphroditic species, flowers have an average of 63.4 ± 6.9 (SD) ovules and 2150.7 ± 965.0 pollen tetrads [72]. There is no correlation between the number of ovules and the number of pollen tetrads in a flower and, on the basis of frequency distributions of ovule and pollen counts, it appears that a shift toward female gender and, thus, gender dimorphism is occurring in wild blueberry [68,72]. Clones exhibit self-incompatibility and require outcrossing [31,[73][74][75], although Bell et al [75] found that 20% of clones have high levels of self-compatibility and that outcrossing was non-reciprocal.…”
Section: Appendix a Literature Review Of Wild-blueberry Reproductive Biology And Pollinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this hermaphroditic species, flowers have an average of 63.4 ± 6.9 (SD) ovules and 2150.7 ± 965.0 pollen tetrads [72]. There is no correlation between the number of ovules and the number of pollen tetrads in a flower and, on the basis of frequency distributions of ovule and pollen counts, it appears that a shift toward female gender and, thus, gender dimorphism is occurring in wild blueberry [68,72]. Clones exhibit self-incompatibility and require outcrossing [31,[73][74][75], although Bell et al [75] found that 20% of clones have high levels of self-compatibility and that outcrossing was non-reciprocal.…”
Section: Appendix a Literature Review Of Wild-blueberry Reproductive Biology And Pollinationmentioning
confidence: 99%
“…Individual flower viability is 8-10 days with maximum stigma receptivity at 1-3 or 4 days, depending upon the year [70]. In this hermaphroditic species, flowers have an average of 63.4 ± 6.9 (SD) ovules and 2150.7 ± 965.0 pollen tetrads [72]. There is no correlation between the number of ovules and the number of pollen tetrads in a flower and, on the basis of frequency distributions of ovule and pollen counts, it appears that a shift toward female gender and, thus, gender dimorphism is occurring in wild blueberry [68,72].…”
Section: Appendix a Literature Review Of Wild-blueberry Reproductive Biology And Pollinationmentioning
confidence: 99%
“…Forests are harvested and the existing understory blueberry plants become established.The underlying genetic diversity of lowbush blueberry is relatively unknown compared to other fruit crops [8]. Recently, a variety of techniques and molecular markers have been used to investigate the genetic heterogeneity and relatedness of V. angustifolium populations [1,8,[10][11][12][13][14][15]. These studies have shown V. angustifolium to be highly diverse in Maine and the Canadian Maritimes.…”
mentioning
confidence: 99%
“…There is still much that is not known about wild blueberry reproduction. Several investigations into the plant role in wild blueberry pollination and plant reproduction have advanced our knowledge into the areas of tradeoffs in reproductive effort investment [21,22], reproductive self-incompatibility/compatibility [17,18,[23][24][25], spatial genetic structure and relatedness [26][27][28], reproductive tissue investment [29], gene flow measured as pollen movement from donor to recipient clone [30,31], timing of flower bud production [9,32] and flowering [9,32], plant plasticity in regards to physiological responses in growth and development and the effects of climate warming on blueberry pollination [33,34]. One topic that has not been researched is the ecology of autogamy in the reproduction of wild blueberry, the focus of this study.…”
Section: Introductionmentioning
confidence: 99%